Prevalence of low back pain in older Brazilians: a systematic review with meta-analysis - Leopoldino,Amanda Aparecida Oliveira (2016)
Abstract Introduction Prevalence of low back pain (LBP) is expected to increase worldwide with aging of the population but its prevalence in older people is not clear, mainly in developing countries. Objective To estimate the prevalence of LBP in older Brazilians. Methods Electronic searches on SciELO, LILACS, MEDLINE, EMBASE and CINAHL, as well as hand-searching identified studies investigating prevalence of LBP in older Brazilians aged 60 years or over. Two independent reviewers selected studies fulfilling the inclusion criteria, assessed risk of bias for each included study and extracted relevant data. Meta-analysis was conducted when enough homogeneity allowed and the GRADE system was used to summarize the overall quality of the evidence. Results Sixteen studies were included with a total of 28,448 participants. Data from point- and period-prevalence of LBP were obtained. Meta-analysis was conducted for 13 studies reporting point-prevalence. Pooled point-prevalence of LBP was 25.0% (95% CI 18.0–32.0). Other three studies investigated period-prevalence: one-week prevalence = 15.0% (95% CI 13.0–18.0); six-month prevalence = 43.0% (95% CI 42.0–44.0); and 12-month prevalence = 13.0% (95% CI 11.0–16.0). Sensitivity analyses were performed for point-prevalence and exclusion of studies with poorer methodological quality tended to increase the estimated prevalence of LBP. Conclusion Moderate-quality evidence showed that at any point in time one in four older Brazilians suffers from LBP. This was the first systematic review investigating nationwide data on the prevalence of LBP in older people and contributes important clinical and epidemiological evidence for policymakers.